Fake News and Information Warfare in the Age of Globalization: ideological Manipulation and Social Consequences - Liu L. (Socio-Economic Processes of Modern Society, 2024)
this article examines the multifaceted issues surrounding the spread of fake news and information warfare in the digital age. Drawing on empirical evidence and theoretical frameworks, it reveals the mechanisms underlying the spread of misinformation, including algorithmic amplification and echo chambers. The implications for society are discussed in detail, including the impact on media credibility, social cohesion, and critical thinking skills.
Keywords: критическое мышление; critical thinking; фейковые новости; fake news; информационная война; information warfare; алгоритмическое усиление; эхо-камеры; доверие к СМИ; algorithmic amplification; echo chambers; media trust